(untitled) (Prilozi za orijentalnu filologiju, 2017)
Since its inception and until its end, the Ottoman Empire gave importance to the positions of the scholars, teachers judges, imams, preachers and muezzins just as it gave importance to the political social military economical and cultural events.During the time of Sultan Abdulhamid II, the records of the government functionaries were written down. The government archives were thus organized in a more systematic fashion. The names of nine scholars and judges of Bosnian background are extant in the Sheikhs Archives of the Istanbul Muftulugu. The oldest goes back to the year 1249 AH while the most recent is dated 1315 AH. The following files are to be found: The Palanka deputy Abdulhamid Efendi, the preacher Halil Efendi in Fatih, the Bosnia Muftu Ibrahim Efendi. The Yanya deputy Lutfullah Efendi, the Sinop-Gerze Muftu Salih Hulusi Efendi, the Uskudar deputy Sâlih Efendi and the Fatih preacher Yusuf Sûdî Efendi. The files indicate the enrollment dates, the various places with their corresponding dates, the salaries and such information. The study of the records puts forward the life of the intellectual class, the administrative organization, the rules applying to the particular positions, the various schools and the events in the intellectual life of the time.